Comparison of Reactor Configurations for Biogas Production from Rapeseed Straw - Xinmei Fu; Yuan Hu (BioResources, 2016)
To investigate the effects of reactor configurations on the anaerobic digestion performance of agricultural residue rapeseed straw, semi-continuous, one-stage, continuously stirred tank reactors (CSTR) and batch, two-stage, leach bed-upﬂow anaerobic sludge blanket (UASB) reactors were operated at the same hydraulic retention time (HRT) (30 days) and target organic loading rate (OLR) (3.0 gVS/L.d). In the continuously loaded CSTR, the specific methane yields did not substantially change as the OLR increased from 1.5 gVS/L.d to 3.0 gVS/L.d during the four periods. Conversely, the specific methane yields in the batch-fed leach bed-UASB increased considerably with the increase in OLR. The leach bed reactor contributed 75% of the total yield, while the UASB reactor contributed only 25% of the total yield. The total specific methane yields were 108 mL/gVS and 160 mL/gVS for the leach bed-UASB and CSTR, respectively, while the volatile solid (VS) reductions of the rapeseed straw were 27.1% and 36.6%, respectively. The results indicated that the process performance was more efficient in the CSTR than in the leach bed-UASB for the digestion of rapeseed straw. Biogas production was clearly affected by the reactor configurations.